2014
DOI: 10.3109/10826084.2014.984847
|View full text |Cite
|
Sign up to set email alerts
|

Development of Risk Perception and Substance Use of Tobacco, Alcohol and Cannabis Among Adolescents and Emerging Adults: Evidence of Directional Influences

Abstract: While there is support for the rationale behind adequate risk perception as a goal of preventive interventions, the possibility of risk reappraisal should not be neglected, especially regarding illicit substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
2
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 74 publications
6
86
2
14
Order By: Relevance
“…Some evidence indi cates enhancing recognition of the haz ards of alcohol use may assist in reducing adolescent binge drinking, and in turn, improve educational attainment. 47 For example, young teenagers with high risk perceptions of substance use were less likely to binge drink as high school seniors, which was associated with greater chances of graduating from high school and attending college. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Some evidence indi cates enhancing recognition of the haz ards of alcohol use may assist in reducing adolescent binge drinking, and in turn, improve educational attainment. 47 For example, young teenagers with high risk perceptions of substance use were less likely to binge drink as high school seniors, which was associated with greater chances of graduating from high school and attending college. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Okaneku et al [18] studied changes in the perception of risks associated with cannabis consumption and found that people who had consumed cannabis in the previous month reported lower risk perception for both regular and occasional consumption. Similarly, the structural equation model developed in Europe by Grevenstein, et al [19] showed that risk perception significantly influences consumption patterns for substances like tobacco, alcohol and cannabis, and proved that changes in risk perception predict future changes in drug use. Moreover, cannabis consumption was also found to influence perception of the risk associated with that substance.…”
Section: Introductionmentioning
confidence: 93%
“…Taken together, our findings and these qualitative studies suggest that perception of heroin risk is a promising candidate risk factor for the initiation of heroin use and related behaviors among NMPO users. We cannot, however, rule out the possibility that perceived risk of heroin decreases following heroin initiation, an effect that has been observed for marijuana use, but not alcohol or tobacco use (Grevenstein, Nagy, & Kroeninger-Jungaberle, 2015). …”
Section: Discussionmentioning
confidence: 95%